Correlation between equine colic and weather changes - DIAKAKIS (Ν. ΔΙΑΚΑΚΗΣ) N.; TYRNENOPOULOU (Π. ΤΥΡΝΕΝΟΠΟΥΛΟΥ) P. (Journal of the Hellenic Veterinary Medical Society, 2018)
The objective of this study is to evaluate the possible correlation between relative humidity/temperature change and equine colic in a specific region of Northern Greece. A study population of 823 adult horses stabled in a 40-km-radius around Thessaloniki, Northern Greece were included in this study; a total of 245 horses, suffering from several types of colic between January 2010 and December 2012 were selected. Metereological data, including temperature (oC) and relative humidity (%) were obtained as 3-hour periodic measurements by the Hellenic National Metereological Service. Statistical analysis was performed using Spearman correlation coefficients in order to assess the relationship between temperature changes, relative humidity changes and equine colic. A positive correlation between temperature change and equine colic was detected during March for the whole 3-year period, while positive correlation was presented during several months of late spring and late fall in specific years. No correlation between changes in relative humidity values and colic was shown. Moreover, a negative correlation between relative humidity and temperature, for temperatures >10°C (rho=-0.568, p<0.01) was found, while, a positive correlation (rho=0.650, p<0.01) between daily temperature difference (ΔT) and relative humidity difference was detected. In this study, abrupt temperature change was proven as a significant risk factor in the development of colic during late spring and fall, in Northern Greece, requiring more vigilant horse owners and equine practitioners. These results suggest that in the future it may be possible to modulate management taking into consideration the current weather conditions, in order to prevent colic episodes.